AGRARIAN DISPUTE RESOLUTION RELATING TO COMMON LAND USE NON-LITIGATION CHANNELS TO REGISTER AREA 45 IN MESUJI: PENYELESAIAN SENGKETA AGRARIA TERKAIT PENGGUNAAN LAHAN BERSAMA MELALUI SALURAN NON-LITIGASI UNTUK MENDAFTARKAN AREA 45 DI MESUJI - Anggalana; Irvan Ramli; Zainab Ompu Jainah (Pusat Studi Konstitusi dan Perundang-undangan, 2026)
The agrarian dispute over customary land in the Register 45 Mesuji Forest Area is a structural conflict involving the state, corporations, and local communities. The verification of production forest areas and the issuance of management permits to private entities without taking into account the rights and existence of the communities that have long managed and used the land are the main causes of this dispute. The current settlement strategy, which has involved coercive measures and litigation, has not worked and has even prolonged the war and exacerbated human rights abuses. The objectives of this study are to evaluate the efficacy of non-litigation dispute settlement, analyze the features of agricultural conflicts in Register 45 Mesuji, and investigate how customary land disputes are resolved in other nations. Statutory, conceptual, and comparative legal techniques are all part of the normative juridical research methodology. The research results of the study demonstrate that agricultural conflicts in Register 45 are complex and cannot be adequately settled by a formal court system alone. Since non-litigation dispute resolution techniques like discussion and mediation promote inclusive discourse, lessen conflict escalation, and uphold community rights, they have a higher chance of achieving substantive justice. Studies comparing South Africa, Brazil, and the Philippines demonstrate that the state's active mediation role and acknowledgement of indigenous peoples' collective rights are essential to the long-term settlement of agricultural disputes. This study suggests a Register 45 conflict resolution approach that uses multi-party mediation focused on restorative justice and human rights protection, temporary acknowledgment of community management rights, and participatory inventory.